PENGARUH MOTIVASI KERJA, KEPEMIMPINAN, PENDIDIKAN DAN PELATIHAN SERTA KEPUASAN KERJA TERHADAP KINERJA KARYAWAN TETAP DI RUMAAH SAKIT GRHA HUSADA - Budiyono Pristyadi; Muhammad Rantau Edy Santoso (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
The purpose of this study to determine the effect of work motivation, leadership, education and training and job satisfaction on the performance of permanent employees in hospital grha husada. This study is a quantitative research. Data collection techniques through the distribution of questionnaires to 48 permanent employees. technical analysis used is multiple linear regression analysis. The results showed that work motivation, leadership, education and training, and job satisfaction have a positive significant affect partially on the performance of permanent employees in the hospital grha husada.